Rhipicephalus sanguineus from Hungarian dogs: Tick identification and detection of tick-borne pathogens - Ghodrati, Sajjad; Lesiczka, Paulina Maria; Zurek, Ludek; Szekely, Farkas; Modrý, David (Veterinary parasitology, regional studies and reports, 2024)
The brown dog tick, Rhipicephalus sanguineus is a complex of tick species with an unsettled species concept. In Europe, R. sanguineus is considered mainly a Mediterranean tick with sporadic findings in central and northern Europe. R. sanguineus is known as a vector of a range of pathogens of medical and veterinary importance, most of which not yet reported as autochthonous in Hungary. A total of 1839 ticks collected by veterinarians from dogs and cats were obtained in Hungary. The study aims at precise determination of ticks identified as R. sanguineus and detection of pathogens in collected ticks. All ticks were morphologically determined and 169 individuals were identified as R. sanguineus. A subset of 15 ticks was selected for molecular analysis (16S rDNA, 12S rDNA, COI). Phylogenetic analyses invariably placed sequences of all three markers into a single haplotype identified as R. sanguineus sensu stricto. All 169 brown dog ticks were tested for the presence of A. platys, E. canis, R. conorii, B. vogeli and H. canis. None of the investigated ticks was positive for the screened pathogens, though A. phagocytophilum sequence was detected in a single tick.
Keywords: RNA, Ribosomal, 16S; Cats; psi; Rickettsia conorii; Dogs; Tick Infestations; mužské pohlaví; Hungary; Dog Diseases; infestace klíšťaty; kočky; nemoci psů; ženské pohlaví; RNA ribozomální 16S; Rhipicephalus sanguineus; zvířata; Ehrlichia canis; fylogeneze; Maďarsko; nemoci přenášené klíšťaty; Tick-Borne Diseases; Female; RNA ribozomální; Phylogeny; RNA, Ribosomal; Anaplasma; Male; Animals